Dexmedetomidine as a Neuroprotective Sedative Agent in Ultrasound-Guided Ulnar Nerve Block for a Patient with Traumatic Brain Injury: A Case Report - Aryanda Widya Tazkagani Salsabila; Heri Dwi Purnomo (HM Publisher, 2025)
Introduction: Traumatic brain injury (TBI) often presents alongside extracranial injuries requiring surgical intervention. General anesthesia in such cases poses significant challenges, particularly in patients with concomitant pulmonary complications. This case report describes the successful use of ultrasound-guided ulnar nerve block combined with dexmedetomidine sedation for a patient with moderate TBI and pulmonary contusion undergoing open reduction and internal fixation (ORIF) of a left-hand finger fracture. Case presentation: A 50-year-old male presented with moderate TBI, pulmonary contusion, and an open fracture of the fifth digit of his left hand following a motor vehicle accident. Due to the risks associated with general anesthesia, an ultrasound-guided ulnar nerve block was performed using levobupivacaine 0.375%. Dexmedetomidine was used as a sedative agent due to its neuroprotective properties and minimal respiratory depressant effects. The procedure was successful, with the patient maintaining stable hemodynamics and adequate sedation throughout the surgery. Conclusion: This case highlights the feasibility and safety of ultrasound-guided peripheral nerve block combined with dexmedetomidine sedation as an alternative to general anesthesia in patients with TBI and pulmonary contusion. Dexmedetomidine's neuroprotective effects and minimal respiratory depression make it a valuable tool in managing such complex cases.